Depressão: aspectos fisiopatológicos e o efeito tipo-antidepressivo da apocinina - Pereira, Gabriele Cheiran (2020)
Depression is considered a public health challenge around the world. According to the World Health Organization, more than 300 million people (approximately 6% of the world population) are affected by this disorder. Considering that depression is closely related to the high rate of death from suicide and that a large number of patients are refractory to any of the available antidepressant agents (between 30 and 50%), understanding the mechanisms involved in its pathophysiology is of great importance, as well as the investigation of new therapeutic alternatives. Thus, the general aim of this work was to investigate the involvement of glucocorticoids, hypothalamic-pituitary-adrenal (HPA) axis, microglia and oxidative stress in the pathophysiology of depression, as well as to evaluate the apocynin antidepressant-like effect. To this end, a review article was first developed covering the involvement and relationship of the microglia and the HPA axis in depression. Subsequently, the chronic corticosterone administration model (CCA) was performed to induce depressive-like behavior (DLB) in mice, as well as to evaluate its effect on the protein expression of the glucocorticoid receptor (GR), brain-derived neurotrophic factor (BDNF) and its receptor, TrkB, in brain structures (prefrontal cortex, hippocampus and striatum). Finally, the effect of apocynin, an antioxidant of natural origin, on the DLB induced by CCA was investigated, as well as its effect on the oxidative profile (enzymes superoxide dismutase, SOD, and catalase, CAT, and on hydrogen peroxide levels, H2O2) after this induction protocol. Through the review article it was possible to suggest that the immune and neuroendocrine systems work in a coordinated way and their deregulation may be involved in psychiatric disorders such as depression, since neuroinflammation and hypercortisolism are often observed in this condition. After CCA, the development of DLB was observed, accompanied by a reduction in the BDNF immunocontent in the prefrontal cortex and an increase in GR and TrkB in the hippocampus of mice. This protocol was also able to reduce the adrenal weight / body weight ratio, suggesting dysregulation of the HPA axis as well as the possible relationship of the glucocorticoid / GR and BDNF / TrkB pathways in the pathophysiology of depression. Moreover, ACC induced an increase in SOD activity and H2O2 levels and a reduction in CAT activity in the three brain structures evaluated. Apocynin treatment was able to reverse both DLB and most oxidative changes after the CCA model, suggesting an antidepressant-like effect. Therefore, the present study suggests that depression has a “multifisiopathological” characteristic, indicates possible altered pathways and still suggests apocynin as a potential agent for the treatment of this disorder.